SOLAR CLUB SENIOR en el municipio del Espinal – Tolima (2023)
The project is developed in the municipality of Espinal, in the department of Tolima. In it municipality we find a lack of equipment where activities can be carried out For the adult population, finally, equipment is proposed that meets the needs of a target population whose social life revolves around activities, which do not influence their stage retirement, through equipment we want to achieve an endless number of services that can satisfy needs and achieve a livable lifestyle, in the same way develops spaces for social integration, recreation spaces and models of inhabiting the living place